2022
DOI: 10.1186/s13256-022-03702-2
|View full text |Cite
|
Sign up to set email alerts
|

Brucellosis with rare complications and review of diagnostic tests: a case report

Abstract: Background Brucellosis is one of the most common zoonotic diseases in the world. Osteoarticular complications, especially vertebral system involvement, are most commonly reported. However, reports and coreports of pulmonary complications and thoracal spondylodiscitis and epidural abscess are rare. Case presentation Spondylodiscitis was detected at the T11–12 vertebral level, followed by epidural and paravertebral abscess, and then empyema was detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
(18 reference statements)
0
1
0
1
Order By: Relevance
“…[ 4 , 14 , 15 ] Brucella was the causative agent in 1 patient with concomitant spondylodiscitis and empyema. [ 16 ] Notably, no previous studies documented SA as the culprit. Although a few cases of secondary spondylodiscitis following oropharyngeal surgery and poor oral hygiene have been reported, [ 1 , 17 ] no study has reported the concomitant occurrence of spondylitis and empyema after oral surgery.…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 , 14 , 15 ] Brucella was the causative agent in 1 patient with concomitant spondylodiscitis and empyema. [ 16 ] Notably, no previous studies documented SA as the culprit. Although a few cases of secondary spondylodiscitis following oropharyngeal surgery and poor oral hygiene have been reported, [ 1 , 17 ] no study has reported the concomitant occurrence of spondylitis and empyema after oral surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Abdominal pain due to inflammatory peritonitis is another possibility which may occur in patients with liver cirrhosis (spontaneous bacterial peritonitis)or rarely as a direct peritoneal infection without cirrhosis [39]. Pain is not only visceral, but also abdominal wall pain in combination with fever and severe low back pain has been reported [40].…”
Section: X-ray Images Showed Multiple Cystic Low Density Areas (Blue ...mentioning
confidence: 99%
“…Сокращение объёмов серологических и бактериологических исследований среди животных и людей, ослабление ветеринарно-санитарного контроля и образование новых частных хозяйств являются препятствием к своевременному выявлению вновь заболевших бруцеллёзом [5]. Значительно затрудняют раннюю диагностику бруцеллёза неспецифичность, «расплывчатость» клинических проявлений и «маски» других заболеваний [6][7][8][9]. В настоящей статье описан случай поздней диагностики бруцеллёза у 10-летнего мальчика.…”
Section: аннотацияunclassified